1999
DOI: 10.1161/01.str.30.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Modification in Stroke Prevention

Abstract: Background and Purpose-We reviewed Stroke Clinic data to determine the extent of risk factor modification achieved in patients with cerebrovascular disease over 2 years. Methods-Visits to the Stroke Clinic of a tertiary medical center from July 1, 1994, through June 30, 1996, were reviewed.Obesity, smoking, hypertension, hyperlipidemia, hyperglycemia, and lifestyle changes were noted in patients with Ն2 visits (nϭ61) and measures (number varied) of these parameters. Results-Fifty-six patients (92%) had primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 32 publications
8
76
3
Order By: Relevance
“…The proportion with hypertension within these samples has been reported to be 60% at 3 months in a community stroke register, 4 56% at 1 year after discharge from a stroke unit, 15 74% in a 1-year follow-up of consecutive patients in a stroke prevention clinic, 5 and 82% within a consecutive sample from a Veteran's Affairs stroke clinic. 16 The greater proportion of people with hypertension in the present study may be attributable to the age difference between the NEMESIS cohort and those in the above-mentioned studies. The mean age of NEMESIS survivors was between 3 and 11 years older than the mean age within the other studies.…”
Section: Discussionmentioning
confidence: 56%
“…The proportion with hypertension within these samples has been reported to be 60% at 3 months in a community stroke register, 4 56% at 1 year after discharge from a stroke unit, 15 74% in a 1-year follow-up of consecutive patients in a stroke prevention clinic, 5 and 82% within a consecutive sample from a Veteran's Affairs stroke clinic. 16 The greater proportion of people with hypertension in the present study may be attributable to the age difference between the NEMESIS cohort and those in the above-mentioned studies. The mean age of NEMESIS survivors was between 3 and 11 years older than the mean age within the other studies.…”
Section: Discussionmentioning
confidence: 56%
“…13 This finding could be explained by both the reported decline in vascular risk in recent years, possibly related to improved vascular preventive measures, 16,17 and limited access to mortality data in our study.…”
Section: Discussionmentioning
confidence: 68%
“…13 However, the neurologists in the clinic relied on the primary-care physicians to prescribe therapy. In a large audit, in the UK, 14 41% of stroke patients achieved their BP target and 61% were still smoking.…”
Section: Discussionmentioning
confidence: 99%
“…89 In one recent study of stroke patients, data from a stroke clinic at a tertiary referral medical center in the United States indicated that during a 2-year period, 90% of patients who were overweight at their initial evaluation remained overweight, only 51% of hypertensive patients had their blood pressure under adequate control, serum lipids and lipoproteins remained abnormal in 55% of patients, none of the smokers quit smoking, and few patients modified their dietary or exercise practices. 90 Clearly, there is an urgent need to bridge the treatment gap by developing and implementing approaches that provide all stroke survivors with affordable access to effective, comprehensive stroke risk-reduction interventions. 91 …”
Section: Barriers To Physical Activity and Exercise Training In Strokmentioning
confidence: 99%